Vulneración de derechos fundamentales al aplicar el principio de proporcionalidad en la prisión preventiva, Distrito Judicial La Libertad – 2021 - Bardales Sánchez, Alexandra Mercedes (2023)
The procedural institution of pretrial detention is becoming increasingly important, its practical incidence has increased enormously, and its automated application is often harshly criticized. For this reason, in the present study we sought to analyze the practical application of the principle of proportionality in the orders that declare the requirement of preventive detention founded, issued in the Judicial District of La Libertad, in the year 2021. In order to achieve this purpose, a detailed study of seven preventive detention orders was carried out in which the request for the filing of this precautionary measure has been declared founded, with this, it was possible to examine the way in which its work has been carried out. application in the Judicial District of La Libertad. In addition to this, some surveys were applied to various legal operators with the aim of being able to gather their perception regarding the practical management of preventive detention, in our Judicial District. The results obtained allowed us to determine that there is an inadequate application of the proportionality test in the preventive detention orders issued by the preparatory investigation judges of Trujillo, in the year 2021, with which it was determined that the right to personal liberty is violated. and the presumption of innocence of the accused.